Penal nationalism in the settler colony: On the construction and maintenance of ‘national whiteness’ in settler Canada - Evans, Jessica (Punishment & society, 2021)
The summer of 2020 was one of unprecedented mass protest and a growing critical awareness around the racist operation of criminal justice systems in North America. Consequently, criminal justice systems have been placed squarely at the forefront of struggles for racial equality and social change. While activists, critical researchers, and legal experts have argued racial justice requires a diversion of communities and resources away from criminal justice systems, the focus in mainstream policy, media, and academic circles has been on reform. In Canada, a focus on reformist responses to this racial violence has been justified through a distorted view of Canada’s criminal justice system. Drawing on the concept of penal nationalism, I argue that Canadian carceral practices must be understood as constitutive of the settler-colonial state and its ideological, material and institutional mooring in racial whiteness as the locus of settler power and sovereignty. To this end, it is not enough to reform specific penal practices, while leaving intact the legitimacy of the criminal justice system in general. What is at stake is the very definition and protection of a national identity, which in the settler colony is predicated on colonial whiteness, Indigenous erasure, and racialized exploitation.